Dahlia campanulata and D. cuspidata (Asteraceae, Coreopsideae): two new species from Mexico - Saar, Dayle E.; Sørensen, Paul D.; Hjerting, J. P. (Instituto de Ecología, A.C., 2003)
Dahlia campanulata and D. cuspidata (Asteraceae, Coreopsideae), two new species from the Mexican states of Oaxaca and Hidalgo, respectively, are described and illustrated. Dahlia campanulata is distinguished by its exceptionally large, pendulous, and campanulate flower heads; leaf petioles with enlarged clasping bases that are much thicker than in any other species of Dahlia; and enormous tubers that exceed 0.5 m in length. Dahlia cuspidata is distinguished by its large outer involucral bracts and cuspidate leaflets, particularly at the terminal end of the rachis and those at the ends of the lateral rachillae; the terminal leaflet on mature leaves is often much more rounded (versus elliptic) than the lateral leaflets.